Macierzyństwo zastępcze: [Surrogate motherhood] (Studia Prawnicze / The Legal Studies, 1993)
Na gruncie ustawodawstwa polskiego o macierzyństwie określonej kobiety rozstrzyga zatem akt urodzenia dziecka, w którym urzędnik USC jest zobowiązany, na podstawie zgłoszenia urodzenia dziecka, umieścić dane dotyczące rodziców (art. 29 p.o a.s.c. w zw. z art. 13 p.o a.s.c. oraz art. 32 p.o a.s.c.). W interesującym nas tutaj przypadku matką dziecka według aktu urodzenia będzie kobieta, która urodziła dziecko, a więc matka zastępcza.Problem jednak z ustaleniem macierzyństwa powstanie dopiero wówczas, gdy jedna z zainteresowanych osób, najczęściej matka genetyczna, będzie kwestionować stan cywilny dziecka ustalony w akcie urodzenia. Na gruncie ustawodawstwa polskiego nie ma wątpliwości, iż powództwo to jest dopuszczalne. Możliwość taka wynika z brzmienia art. 189 k.p.c., art. 86 k.r.i o. oraz art. 453 k.p.c.Akt urodzenia dziecka zostanie sporządzony zgodnie z zasadą, iż matką dziecka jest kobieta, która je urodziła. Zmiana zaś stanu cywilnego dziecka jest możliwa wyłącznie w następstwie procesu o zaprzeczenie macierzyństwa kobiety wpisanej, jako matka do aktu urodzenia dziecka. W tej sytuacji decyzja co do macierzyństwa jednej z tych kobiet należy do sądu. Opowiedzenie się jednak za uznaniem macierzyństwa dawczyni komórki jajowej może doprowadzić do destabilizacji raz ustalonego stanu cywilnego dziecka, zważywszy, iż w grę wchodzi ocena wartościująca in casu te dobra, które w zasadzie są niewymierne. Z tych to przyczyn należy opowiedzieć się de lege lata za macierzyństwem kobiety, która urodziła dziecko. According to Polish legal acts, the motherhood status of a specific woman is decided by the birth certificate of the child, in which the registrar is obliged to provide the data of the parents according to the notification of the child’s birth (Article 29 p.o a.s.c. in relation to Article 13 p.o a.s.c. and Article 32 p.o a.s.c.). In the case we are interested in here, the mother of the child as specified in the birth certificate will be the woman who gave birth to the child, namely the surrogate mother.However, the problem of establishing the motherhood will only arise when one of the persons concerned, most often the genetic mother, disputes the marital status of the child as established in the birth certificate. According to Polish legislation, there is no doubt that this claim is admissible. This option results from the wording of Article 189 of the Civil Procedure Code, Article 86 of the Family and Guardianship Code and Article 453 of the Civil Procedure Code.The birth certificate of the child will be drawn up in accordance with the principle stating that the mother of the child is the woman who gave birth to the child. A change in the marital status of the child is only possible following a lawsuit intended to deny the motherhood of the woman entered in the child's birth certificate as the mother. In these circumstances, it is up to the court to decide on the motherhood of one of these women. However, opting to recognise the motherhood status of the oocyte donor may lead to destabilisation of the already established marital status of the child, given that what is at stake is an in casu valuation of these values, which are unquantifiable in principle. For these reasons, it is necessary to advocate de lege lata for the motherhood of the woman who gave birth to the child.